It divide 11÷22=2 and if you subtract it will be 11-22=11.please give me a like.
Answer:
3x² - 9x + 5
Step-by-step explanation:
Given
(5x² - 3x + 4) - (2x² + 6x - 1)
Distribute the first parenthesis by 1 and the second by - 1
= 5x² - 3x + 4 - 2x² - 6x + 1 ← collect like terms
= (5x² - 2x²) + (- 3x - 6x) + (4 + 1)
= 3x² - 9x + 5
Incorect, you messed up on the second step. 7x4x is not 7x, it is 28x.
We claim that the answer is
Since the two graphs both open down, and all the answer choices, in addition to the equation of the blue graph, are quadratic polynomials, the leading coefficient must be negative. This immediately rules out answer choices A, B, and C, leaving D as the answer.